Pengaruh Struktur Kepemilikan dan Dewan Komisaris Terhadap Kinerja Bank Umum Konvensional Yang Menyalurkan Kredit Pada UMKM: Dengan Pengungkapan Corporate Social Responsibility Sebagai Mediasi - Ribka Gwijangge; Sri Ayem; Anita Prismatiwi (Politeknik Negeri Jember, 2021)
This research aims to examine the effect of institutional ownership, public ownership, board of commissioners, CSR on the performance of Conventional Commercial Banks that disburse loans to MSMEs and examine the effect of institutional ownership, public ownership, board of commissioners on CSR disclosure of Conventional Commercial Banks that disburse loans to MSMEs. This research used is associative quantitative research, the sample used is conventional banks that distribute MSME loans listed on the Indonesia Stock Exchange (IDX), using purposive sampling technique. The data used is secondary data, the data source comes from the documentation of the financial statements of conventional banks that channel MSME loans and are listed on the Indonesia Stock Exchange in 2017-2019. The data analysis technique used multiple linear regression method. The results of this research indicate that institutional ownership has no effect on bank performance. Public ownership, board of commissioners, CSR, have a positive effect on the performance of the Bank. Institutional ownership, public ownership, the board of commissioners have a positive effect on the Bank's CSR. Keywords: Institutional And Public Ownership, Board Of Commissioners, CSR, Performance Of Conventional Commercial Banks